CoNaMad—Cohorte de Nacimiento de Madre de Dios/Madre de Dios Birth Cohort to Study Effects of in-utero Trace Metals Exposure in the Southern Peruvian Amazon. Issue 1 (19th July 2021) - Pan, William K.; Weinhouse, Caren; Ortiz, Ernesto J.; Berky, Axel J.; Fixsen, Emma; Mallipudi, Andres; Feingold, Beth J.; Navio, Suzy; Rivera, Nelson A.; Hsu-Kim, Heileen; Miranda, J. Jaime
Background: In-utero exposure to mercury and other trace metals pose a significant threat to child health and development, but exposures and health impacts in artisanal and small-scale gold mining (ASGM) environments are poorly defined. Objectives: We describe the CONAMAD study design, a prospective birth cohort consisting of multiparous women (18 and over) living in rural and peri-urban Peruvian Amazon communities exposed to ASGM. Methods: Pregnant women are enrolled from health posts across four zones of Madre de Dios, Peru. Data are collected at enrollment, childbirth, and (planned) 36-48 months. At enrollment, hair samples for mercury assessment, demographic and clinical data are obtained. At birth, we obtain venous and cord blood, placenta, hair, toenails, and saliva. Findings: Two hundred seventy mothers were enrolled at an average 20 weeks gestational age with no differences in maternal characteristics across zones. Two hundred fifteen mothers were successfully followed at birth. We obtained 214 maternal and cord blood samples, 211 maternal and 212 infant hair samples, 212 placenta samples, 210 infant saliva samples, and 214 infant dried blood spots. Data collected will allow for testing our primary hypotheses of maternal malnutrition modifying ratios of cord:maternal blood total mercury (tHg), cord blood:maternal hair tHg, and infant:maternal hair tHg, and whether chemical mixtures (Hg, Pb, Cd) have synergistic effects on infant neurodevelopment. Conclusions: CONAMAD is designed to collect and store samples for future processing and hypothesis testing associated with in-utero mercury exposure and child development. We have completed the exposure assessments and will conduct a follow-up of mothers to evaluate early child development outcomes, including developmental delay and growth. These data offer insights into disease mechanisms, exposure prevention, and policy guidance for countries where ASGM is prevalent.